T Cell Immunity and Zika Virus Vaccine Development. Issue 8 (August 2017) - Lima, Noemia S.; Rolland, Morgane; Modjarrad, Kayvon; Trautmann, Lydie
Abstract : The recent Zika virus (ZIKV) epidemic has created an urgent need for a safe and effective vaccine. There is still a dearth of knowledge about ZIKV immunity, but years of investigation into the immunobiology of other flaviviruses has helped to accelerate the development of a ZIKV vaccine. Although the humoral immune response generates the primary correlate of protection from disease, robust T cell responses could enhance ZIKV vaccine efficacy. Additionally, pre-existing immunity to related flaviviruses could generate cross-reactive T cells that may affect immune responses upon vaccination. In this review, we summarize the key discoveries in the area of flavivirus T cell immunity and postulate on how these findings can inform ZIKV vaccine strategies for inducing protective immunity. Trends: T cell responses are important for clearance of neurotropic flaviviruses from the central nervous system and might also be required for ZIKV. T cells are stimulated upon flavivirus infection and can not only contribute to protection, but also drive immunopathogenesis. Conservation between ZIKV epitopes and other flaviviruses, especially Dengue virus (DENV), might induce cross-reactive T cells. Preclinical and clinical studies are conducted in parallel to develop a vaccine and understand the biology of ZIKV infection, contributing to the accelerated pace of new knowledge gained relating to ZIKV immunity. ZIKV vaccine candidates that have shown protection in mice and nonhuman primates induced modest levels of T cell responses. Scientific knowledge gained from studies on ZIKV T cell immunity will help the rational design of strategies aimed at increasing T cell immunity that could improve ZIKV vaccine efficacy.